CAUSES OF KIDNEY TRANSPLANT DYSFUNCTION AND METHODS OF ITS CORRECTION - M.K. GULOV; B.S. PIROV (Avicenna Tajik State Medical University, 2017)
The severity of the ischemia-reperfusion injury, the prognosis of survival, and the duration of renal allograft functioning have significant value. The use of new non-invasive methods for diagnosis of renal allograft dysfunction and the complex use of various drugs to improve its function create the prerequisites for preventing ischemia-reperfusion injury.